Which Version of the Twelve Prophets Should Christians Read? A Case for Reading the LXX Twelve Prophets - Lim, Bo H. (Journal of theological interpretation, 2013)
The question of which Bible to read continues to be fundamental to the exegetical and theological task. Recent research into the Twelve Prophets has demonstrated that individual books ought to be read in light of their placement within the collection. In the ancient Hebrew and Greek manuscripts, the order of the Twelve Prophets differs, resulting in varying theologies between the versions. The question for Christian interpreters is which text they should read. Scholars have largely favored the MT version of the Twelve and questioned the integrity of a LXX Twelve collection. In this essay, I argue that, as Christian Scripture, books within the Twelve ought to be read in light of their function within both Hebrew and Greek versions. This view rests on a broader theological understanding of canon, as well as recent research on the Twelve Prophets among historical critics. The books of the LXX Twelve consistently appear in the same order in the ancient manuscripts, which suggests that their sequence functioned in a normative manner. LXX Twelve possesses its own catchwords and thematic development that unify the collection and contribute to its distinct theological emphasis. If the Holy Spirit sanctifies the canonical process from composition to reception, then a more expansive canon can include both versions. In addition, if ecclesiastical tradition ought to be consulted in canonical decisions, the exegetical practices of Augustine and Jerome provide a precedent for using both versions for Christian theological interpretation.